CHANGES IN SUBSTITUTION OF BANK LOANS AND EU SUBSIDIES IN POLISH BUSINESSES - Paulina Filip (Polityki Europejskie, Finanse i Marketing)
The aim of the article was to determine the degree of bank loan replacement by Polish businesses after profiting from EU help. The identification of similarities and differences was made amonggroups of enterprises that benefit or not from the state aid in the EU’s successive financial perspectives, over the years 2007-2017. Changes in companies’ assets and performance, andvariables referring to the financial effectiveness, were analyzed. The logit model was used in order to define characteristics that have influence on the significance of determinants of financing withpublic subsidies. The cross-sectional nature of data allows for identification of a positive statistical relationship between subsidies and bank loans in medium-sized enterprises. In the course of the study it was established that companies receiving the state aid reduced their share of bank credits on balance sheet totals, as well as indebtedness in total. Over a period of time, thesubsidizing has increased the importance and scope of using bank loans. State aid resources were used as a complementary source of capital for enterprises.